“Comparison of Specific Hip Strengthening Exercises and Conventional Knee Exercises on Pain, Muscle Strength and Function in Sprinters with Patello-Femoral Pain Syndrome” - Mahnoor Asif, Yasha Sajjad, Ali Asad Naeem, Noman Ghaffar, Tahzeem Riaz, Abdul Mannan, Sadaf Waris, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study is to compare the effects of strengthening exercises of Hip and conventional Knee exercises on pain, muscle strength and functional status in sprinters with Patello femoral pain syndrome Methodology: A randomized controlled trial was performed on 28 sprinters. Participants were selected through non-probability convenient sampling. The study was single blinded and was completed in 6 months. The assessor was unaware of the treatment given to both groups. Group 1 received Conventional knee exercises and weight bearing hip strengthening exercises and Group 2 received traditional knee exercises and strengthening exercises of hip with resistance. All Exercises were performed with 12 reps and 3 sets, 3 times a week for 6 weeks. Numeric Pain Rating Scale (NPRS) for pain, AKPS (anterior knee pain scale) for functional status and make test applied through hand held dynamometer measured strength through contractions of knee muscles. Results: The mean age of individuals in interventional group is 22.79 ±4.28 and the individuals in control group is 24.07 ±4.51. Both groups showed significant improvements in pain, function and muscle strength with p<0.05. There were not any significant changes in both groups with p>0.05. Conclusion: Both interventions are equally effective in reducing pain, improving strength and function in sprinters with PFPS which showed that these interventions can be included in the rehabilitation plan of these athletes.